The effects of flooding on dioxin and PCB levels in food produced on industrial river catchments. (April 2015) - Lake, Iain R.; Foxall, Christopher D.; Fernandes, Alwyn; Lewis, Mervyn; Rose, Martin; White, Oliver; Lovett, Andrew A.; White, Shaun; Dowding, Alan; Mortimer, David
Abstract: This research examined the effect of regular flooding upon PCDD/F and PCB levels in milk, beef and lamb, produced on the floodplains of industrial river catchments. Our unique dataset included more than 200 samples analysed for PCDD/Fs and PCBs over two data collection phases (1998–1999 & 2008–2010) from working farms. A robust paired study design was adopted with samples taken from flood-prone farms and nearby control farms not subject to flooding. On industrial river catchments regular flooding is associated with higher PCDD/F and PCB levels in soils and grass. This contamination may be transferred to food but the impact varied by food type. These contrasts may be due to physiological differences between animals, the ages at which they are sent to market and differences in animal husbandry. To minimise the risks of producing food on flood-prone land in industrial river catchments, as well as on any land with elevated PCDD/F and PCB levels, this research suggests a number of options. The choice of livestock may be important and as an example in our study beef cattle accumulated PCDD/Fs to a higher degree than sheep. Land management may also play a role and could include minimising the time that livestock spend on such land or feeding commercial feed, low in PCDD/Fs and PCBs, where appropriate. Highlights: Flooding transfers Dioxins & PCBs to soil and grass in industrial river catchments. Transfer of this contamination to food varies by livestock type. Choice of livestock plays a role in the risk management of contaminated land. Use of commercial feed & land exclusion are other risk management options.